Burnout of Students in Distance Learning During the Covid-19 Pandemic - Ilham Arvan Junaidi; Rury Rizhardi; Endie Riyoko; Rani Mega Putri (AL-ISHLAH: Jurnal Pendidikan, 2022)
With the decline in covid-19 cases and facing the transition from pandemic to endemic, it requires people to be able to maintain health to avoid the terror that is very real for people in the world. As a result of this incident, many countries are reorganizing the paralysis of the economy, society, sports, health, and education. In the world of education, especially in universities, lecturers are required to adapt learning to situations and needs, one of which is through the presentation of material online attractively and attractively according to students so that students will continue to be enthusiastic in the lecture process. Distance learning, carried out from home online, if carried out continuously without presenting attractive, creative, and innovative material from lecturers, is feared to cause negative impacts for students, such as psychological effects, one of which is burnout. The purpose of this study was to determine the level of burnout of students during remote learning during the COVID-19 pandemic. The method used in this study was a survey. The subjects in this study were students of the physical education study program at PGRI Palembang University. Data collection techniques using Burnout questionnaires that are distributed to respondents online with the help of google form.